Increasing airway obstruction from 8 to 18 years in extremely preterm/low-birthweight survivors born in the surfactant era. Issue 8 (6th September 2016) - Doyle, Lex W; Adams, Anne-Marie; Robertson, Colin; Ranganathan, Sarath; Davis, Noni M; Lee, Katherine J; Cheong, Jeanie L
Abstract : Background: The evolution of airway obstruction into late adolescence of extremely preterm (gestational age <28 weeks) or extremely low-birthweight (birth weight <1000 g) survivors in the era after surfactant was introduced is unclear. Objective: To compare changes in spirometry from 8 to 18 years of age of a geographical cohort of preterm survivors with normal birth weight controls, and to determine higher risk groups within the preterm cohort. Methods: Of 297 extremely preterm/low-birthweight survivors born in 1991–1992 in the state of Victoria, Australia, 81% and 70% had spirometry at 8 and 18 years of age, respectively. Corresponding rates among 260 normal birth weight controls were 80% and 58%, respectively. Data were analysed using linear mixed models. Results: The preterm group had substantial impairments in airflow at both ages compared with controls (eg, mean differences in z-score for FEV1 ; 8 years −1.02, 95% CI −1.21 to −0.82; 18 years −0.92, 95% CI −1.14 to −0.71). The preterm group had a greater increase in small airway obstruction between 8 and 18 years compared with controls. Within the preterm group, those who had bronchopulmonary dysplasia in the newborn period and those who were smokers at 18 years had airway obstruction that increased over time compared with those who did not. Conclusions: Preterm survivors born in the surfactant era had significant impairments in airflow through childhood into late adolescence that increased over time compared with controls. At-risk preterm participants include those who had bronchopulmonary dysplasia, and smokers at 18 years.